Clinical outcomes of ectopic pregnancy - Malik, Roopa; Jain, Shaveta; Duhan, Nirmala; Sirohiwal, Daya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy (EP) is a life threatening gynaecological emergency, and a significant cause of maternal mortality and morbidity worldwide. Aim of this study was to determine and evaluate the incidence, clinical presentation, risk factors, management strategies and outcome of the patients with EP. Methods: This was a prospective study of all cases of ectopic pregnancies admitted and managed at PGIMS Rohtak over a period of 1 year. All patients admitted through accident and emergency unit as well as the gynaecology clinic that were managed in gynaecological ward were included in the study. The diagnosis of EP was made by history, clinical examination, urinary pregnancy test and ultrasound examination. Patients were managed as per hospital protocol and relevant data on age, parity, clinical presentation, risk factors, management and findings at laparotomy, and the outcome of treatment were collected. Results: The incidence of ectopic pregnancy in this study was 1.056%. The mean age of the patients was 27±3 years. Of the 102 ectopic pregnancies, 86 (84.31%) were ruptured ectopic pregnancies, while 16 (15.68%) were unruptured ectopic pregnancies. The commonest clinical complaint was abdominal pain (97 of 102, 95.09%) History of previous abortion (induced or spontaneous) was the commonest risk factor (92 of 102, 90.19%) followed by past history of pelvic inflammatory disease (56 of 102, 54.90%). History of tubal surgery was present in 27 of 102 patients (26.47%). commonest surgical procedure done was emergency laparotomy followed by salpingectomy (67 of 102, 65.68%). Conclusions: EP is an important cause of maternal morbidity and mortality in early pregnancy and has remained a reproductive health challenge. Early diagnosis and treatment can improve reproductive outcomes.